Identification of Caffeic Acid Phenethyl Ester (CAPE) as a Potent Neurodifferentiating Natural Compound That Improves Cognitive and Physiological Functions in Animal Models of Neurodegenerative Diseases - Konar, Arpita; Kalra, Rajkumar Singh; Chaudhary, Anupama; Nayak, Aashika; Guruprasad, Kanive P.; Satyamoorthy, Kapaettu; Ishida, Yoshiyuki; Terao, Keiji; Kaul, Sunil C.; Wadhwa, Renu (Frontiers in Aging Neuroscience, 2020)
Cell-based screening of bioactive compounds has served as an important gateway in drug discovery. In the present report, using human neuroblastoma cells and enrolling an extensive 3-step screening of 57 phytochemicals, we have identified Caffeic Acid Phenethyl Ester (CAPE) as a potent neuro-differentiating natural compound. Analyses of control and CAPE-induced neuro-differentiated cells revealed (i) modulation of several key proteins (NF200, MAP-2, NeuN, PSD95, Tuj1, GAP43, and GFAP) involved in neurodifferentiation process, and (ii) attenuation of neuronal stemness (HOXD13, WNT3, Msh-2) and proliferation (CDC-20, CDK-7, BubR1) promoting proteins. We anticipated that the neurodifferentiation potential of CAPE may be beneficial for the treatment of neurodegenerative diseases and tested it using the Drosophila model of Alzheimer’s disease, and mice model of amnesia/loss of memory. In both models, CAPE exhibited improved disease symptoms and activation of physiological functions. Remarkably, CAPE-treated mice showed increased levels of neurotrophin-BDNF, neural progenitor marker-Nestin, and differentiation marker-NeuN, both in the cerebral cortex and hippocampus. Taken together, we demonstrate the differentiation-inducing and therapeutic potential of CAPE for neurodegenerative diseases.